Mazabraud's Syndrome: A Case Report and Up-To-Date Literature Review - Vescini, Fabio; Falchetti, Alberto; Tonelli, Veronica; Carpentieri, Maria; Cipri, Claudia; Cosso, Roberta; Kara, Elda; Triggiani, Vincenzo; Grimaldi, Franco (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Objective: Mazabraud's syndrome is a rare form of bone fibrous dysplasia associated with intramuscular myxomas. Fibrous dysplasia, is generally localized to pelvis and femur and it results in a fragile bone with deformities, pain, pathological fractures and functional impairment. Intramuscular myxomas, are rare benign mesenchymal neoplasms that exceptionally may evolve to malignant forms. Methods: This case report describes a 66-year-old woman with Mazabraud’s Syndrome (MS), characterized both by monostotic right femur fibrous dysplasia and by a solitary intramuscular myxoma at the right quadriceps muscle, that underwent a long-term treatment (4 years) with intravenous zoledronic acid. Results: Zoledronic acid therapy rapidly lowered bone pain together with a reduction of intramuscular myxoma volume, but did not affect the extension of fibrous dysplasia. No adverse effects have been observed during treatment. Conclusion: Highly active bisphosphonates are commonly used for the treatment of bone metabolic disorders and they are generally well tolerated. Zoledronic acid may represent a promising alternative to surgical intervention in MS, although its use in rare form of bone fibrous dysplasias is still controversial.
Keywords: GNAS1 gene mutations